Studies of the Properties and Microstructure of Heat Treated 0.27% C and 0.84% Mn Steel - Mohamed, M. I. (Engineering, Technology & Applied Science Research, 2018)
In the present work, different heat treatments like hardening with different cooling rates followed by tempering at different temperatures have been performed. The material used in this study is carbon steel of 0.27% C and 0.84% Mn. Samples of as-rolled steel were subjected to different heat treatment processes. The steel was heated to the austenitizing temperature of 870°C for 2hrs followed by water quenching, oil quenching, air and furnace cooling. Water and oil quenched samples were subjected to tempering for one hour at temperatures of 250°C, 350°C, 450°C and 550°C. Tensile and impact tests were carried out for as rolled and heat-treated steel. Results show that the heat treated steel revealed an excellent combination of tensile strength and impact strength, which is suitable for structural applications. Optical metallographic investigation was carried out for all samples compared with the as rolled steel. The heat treatment revealed remarkable changes in steel morphology and mechanical properties.